Artificial cephalic deformations in the old Perú. - Borja Villanueva, César Andrés (2006)
The artificial cephalic deformations in humans have remote beginning and they spread in all the continents, in South America, the Peru constitutes the place where the most varied and incredible forms were presented. The reasons for which our ancestors carried out these deformations are not clear and they can be many, from the aesthetic, ethical approaches, of social, economic, moral, magic differentiation, religious, like foreign currency of towns, etc. ln Peru they group in two big filums: deformed by llautu and for cuna. Each one of them with their variants and with their own cultural associations, and this characteristic offers them the corresponding historical location. The artificial cephalic deformations observed in the Peruvian skulls produced craneofacials asymmetries not altering alone the forms but also their growth and development, this way produced the acortación of the structures like skull base, maxillary and displasias skeletal anteroposteriores.